2014
DOI: 10.1371/journal.pone.0113504
|View full text |Cite
|
Sign up to set email alerts
|

The Xylella fastidiosa PD1063 Protein Is Secreted in Association with Outer Membrane Vesicles

Abstract: Xylella fastidiosa is a gram-negative, xylem-limited plant pathogenic bacterium that causes disease in a variety of economically important agricultural crops including Pierce's disease of grapevines. Xylella fastidiosa biofilms formed in the xylem vessels of plants play a key role in early colonization and pathogenicity by providing a protected niche and enhanced cell survival. Here we investigate the role of Xylella fastidiosa PD1063, the predicted ortholog of Xanthomonas oryzae pv. oryzae PXO_03968, which en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…oryzicola (Qian et al ., ) and the commensal Stenotrophomonas maltophilia (McCarthy et al ., ), and have been shown to be essential for virulence, biofilm formation, motility and EPS production. However, the Ax21 homologue in Xylella fastidiosa was shown not to be required for virulence or biofilm formation, supporting the species‐specific evolution of QS signal‐mediated regulation of virulence (Pierce et al ., ).…”
Section: Qs In Plant Pathogensmentioning
confidence: 97%
“…oryzicola (Qian et al ., ) and the commensal Stenotrophomonas maltophilia (McCarthy et al ., ), and have been shown to be essential for virulence, biofilm formation, motility and EPS production. However, the Ax21 homologue in Xylella fastidiosa was shown not to be required for virulence or biofilm formation, supporting the species‐specific evolution of QS signal‐mediated regulation of virulence (Pierce et al ., ).…”
Section: Qs In Plant Pathogensmentioning
confidence: 97%
“…In contrast, in trans unsaturated fatty acids, the kink adds up to only 6° (Macdonald et al 1985 ). Thus, compared to the cis isomers, trans fatty acids can align more closely to each other and in this regard resemble saturated fatty acid residues (Heipieper et al 2003 ; Kulig et al 2016 ; Pierce et al 2014 ). Consequently, this results in a more rigid membrane (Chen et al 1995 ; Diefenbach et al 1992 ).…”
Section: Cis-trans -Isomerization Of Membrane Fatty Acidsmentioning
confidence: 99%
“…It was found that these proteins show different patterns of distribution in the xylem during biofilm formation [ 127 ]. Furthermore, haemagglutinin adhesion and MopB, an outer membrane protein, have been studied in X. fastidiosa [ 120 , 128 , 129 , 130 ]. While the role of the protein (MopB) is not well known, it is well established that the outer membrane proteins (OMPs) in Gram-negative bacteria play vital roles such as (1) keeping the structural integrity of the outer membrane (OM), (2) recognition proteins, (3) transportation, (4) membrane pores, (5) membrane-bound enzymes or components of signal cascades [ 131 , 132 , 133 , 134 ], (6) stress resistance (implicated are Escherichia coli OmpA and OprF in Pseudomonas aeruginosa ) [ 135 , 136 , 137 ], (7) pathogenesis (for example, OmpA in Escherichia coli and OspC in Borrelia burgdorferi ) [ 134 , 138 , 139 ], and (8) agglutination.…”
Section: Ribosome Display Technology In Disease Diagnostics and Comentioning
confidence: 99%